Analisis Mutu Fisik dan Kimia serta Uji Aktivitas Antioksidan Teh Cascara dari Kulit Kopi Arabika (Coffea arabica L.) Asal Papua - Septiani Mangiwa; Diana M. Abulais; Oktafani Patiung; Qonita A. Nisa (Jurnal Biologi Papua, 2023)
Several important chemical components are still present in coffee skin, although they have not yet been put to much use. This study aims to determine the physical and chemical quality as well as the antioxidant activities of cascara tea, which is produced from the skin of Papuan arabica coffee. Coffee skins are gathered by The Highland Roastery Café from several Papuan coffee producers. Cascara is used to make tea, which is packaged in tea bags after being sun-dried. The analysis of physical and chemical quality is in accordance with SNI 3753: 2014. Physical and chemical quality parameters for tea include the condition of the steeping water, moisture content, ash content, crude fiber, phytochemicals, polyphenols, and caffeine levels. It is possible to measure antioxidant activity using the DPPH technique. The physical and chemical characteristics of cascara tea manufactured from Papuan arabica coffee skins are as follows: typical brewing water conditions, moisture content, total ash content, and crude fiber are all 13.00 ± 0.11%, 10.96 ± 0.12%, and 40.55 ± 0.14%, respectively. Phytochemical screening showed that cascara tea contains alkaloids, terpenoids, saponins, and polyphenols, with a total polyphenol content of 1.33 ± 0.05% and caffeine of 0.44 ± 0.05%. Cascara Papua tea exhibits strong levels of antioxidant activity with an IC50 of 13.96 ppm. Therefore, it can be concluded that cascara tea, which is made from arabica coffee skins from Papua and sun-dried, has a physical and chemical quality that complies with the standards. and can be used as an antioxidant beverage to increase endurance. Key words: cascara; coffee skin; arabica coffee; physical and chemical quality; antioxidant.